2021
DOI: 10.3390/nu13082739
|View full text |Cite
|
Sign up to set email alerts
|

Association between Emotional Eating and Frequency of Unhealthy Food Consumption among Taiwanese Adolescents

Abstract: Emotional eating is one factor that increases the consumption of unhealthy food. This study aimed to investigate the association between emotional eating and frequencies of consuming fast food, high-fat snacks, processed meat products, dessert foods, and sugar-sweetened beverages (SSBs) in adolescents. The baseline survey data (2015) from the Taiwan Adolescent to Adult Longitudinal Study (TAALS) were fitted into multivariate logistic regression models adjusted for sex, school type, Body Mass Index (BMI), eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 78 publications
(91 reference statements)
4
27
1
Order By: Relevance
“…Evidence suggests that depression in adolescents may be associated with risky behaviors such as insufficient levels of physical activity [ 11 , 12 , 13 , 14 ], psychoactive substance use [ 15 ], unhealthy eating habits [ 16 , 17 , 18 ], and risky sexual behavior [ 19 , 20 ]. Experts argue that there may be a positive relationship between physical activity and brain health in adolescents, which involves both cognitive function and mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that depression in adolescents may be associated with risky behaviors such as insufficient levels of physical activity [ 11 , 12 , 13 , 14 ], psychoactive substance use [ 15 ], unhealthy eating habits [ 16 , 17 , 18 ], and risky sexual behavior [ 19 , 20 ]. Experts argue that there may be a positive relationship between physical activity and brain health in adolescents, which involves both cognitive function and mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another study conducted with adolescents, there was determined a relationship between emotional eating and these foods [30]. In this study, it was found that individuals who consume both fast food and sugary drinks at least once a week have higher scores for uncontrolled eating, dietary disinhibition, and hunger.…”
Section: Discussionmentioning
confidence: 67%
“…Food and nutrition knowledge (Feyzabadi et al, 2017;Subedi & Bhusal, 2021;Upreti et al, 2021) and self-efficacy (Feyzabadi et al, 2017) are revealed as significant determinants of JFC. Behavioral aspects include smoking, drinking, physical activity, sedentary lifestyle, changing lifestyle, and eating habits (Bui et al, 2021;Li et al, 2020;Silva et al, 2021) are found to be significant determinants of JFC. Of the 22 studies, taste and pleasure of eating junk foods remain the most common intrapersonal level (microsystem) factors that appeal to JFC.…”
Section: The Intrapersonal Factors: Microsystem Influencesmentioning
confidence: 97%